Pengaruh Kualitas Produk, Harga, Dan Promosi Terhadap Keputusan Pembelian Sabun Cuci Muka Kahf (Studi Kasus Di Watsons Summarecon Mall Bekasi) - Kresnadi, Muhammad Faisal; Saing, Bungaran; Sudiantini, Dian (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
Online purchases have skyrocketed since 2020, influenced by the COVID-19 pandemic, and are projected to continue growing to reach USD 16 billion by 2028. This trend indicates that digital shopping for facial cleansing products has become a permanent habit among Indonesian consumers.This study aims to determine the effect of product quality, price, and promotion on purchasing decisions for Kahf facial wash soap at Watsons Summarecon Mall Bekasi. This study uses a quantitative method with a survey approach. Data were collected by distributing questionnaires to 85 respondents who were male consumers aged 17–30 years who had purchased Kahf products at the research location. Data analysis was carried out using multiple linear regression tests with the help of SPSS software version 25. The results of the study showed that partially and simultaneously, the variables of product quality, price, and promotion had a positive and significant effect on purchasing decisions. Product quality has the most dominant influence compared to other variables. The coefficient of determination (Adjusted R²) value of 0.443 indicates that 44.3% of the variation in purchasing decisions can be explained by these three variables, while the rest is influenced by other factors outside the model.